Mohe Dusa: Konstruksi Akuntansi Kerugian - Thalib, Mohamad Anwar (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2019)
The purpose of this study is to construct loss accounting practice by traditional tranders in Gorontalo. This research uses spiritual paradigm. The approach used is Islamic ethnometodology. The stages of data analysis are amal; ilmu; iman; informasi wahyu, and ihsan (amiiin). The results of study found three loss accounting practices; first, reducing the amount of cake sales; second, barter system; third, distributing cakes to local residents. These accounting practices are driven by spirit of patience, tolerance, mutual help, and sharing. These spirits live because of fear of sinning (mohe dusa).